Analisis Morfofonemis Kata Kerja Berprefiks Nasal dalam Cerpen Banjar; Kambang Kada Sakaki (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Using information from Y. S. Agus Suseno's short narrative Kambang Kada Sakaki, this research explores the morphophonemic features of verbs with nasal prefixes in the Banjar language. The study centers on the prefixes maN- and paN-, which are traditionally known as productive affixes in the creation of active verbs. The goal of this research is to provide a clear explanation of the sound changes brought about by the affixation process, including nasal assimilation, phoneme melting, and initial consonant deletion. The methodology used includes data recording and documentation strategies, as well as a case study approach and descriptive qualitative analysis. Identifying verbs with nasal prefixes, categorizing surface forms, and deciphering sound change patterns are all parts of the analysis process. According to the findings, of the 30 verbs examined, 15 exhibit nasal assimilation, 10 experience phoneme melting, and 5 display initial consonant deletion. Depending on the phonological environment of the stem, nasal assimilation patterns reveal the phoneme /N/ shifting to [m], [n], [ŋ], and [ɲ]. The text did not include any data beginning with the prefix paN-, thus the study concentrated on the prefix maN-. This result supports the notion that the prefix maN- is very productive in Banjarese and that there is a strong connection between morphological and phonological processes in the creation of active verbs.